When Do Politicians Appeal More Broadly? A Comment on Chin (2023) - Pijus Krūminas; Simonas Čepėnas; Valdonė Darškuvienė (Institute for Replication (I4R), 2024)
Moya Chin's (2023) paper argues that politicians in two-round majoritarian systems have to appeal more broadly than those in single-round elections. The author uses data for mayoral elections in Brazil. The key findings of the paper conclude that of two-round systems (1) fostering inclusiveness, (2) resulting in higher levels and wider distribution of public goods, and (3) leading to better immediate societal outcomes in terms of drop-out and elementary literacy rates. The author uses regression discontinuity design to test her hypotheses. We test computational reproducibility and successfully duplicate the key results of the study. We also test for result replicability by modifying the data sample used by Chin (2023) using the same method. In nearly all cases, we find that our results are very close (in terms of direction of effect, magnitude, and statistical significance) to those obtained by the original author with only some relationships losing statistical significance. We reproduce and then replicate all the three key empirical results obtained by the author, meaning that there is an effect on inclusiveness, distribution of public goods, and more immediate societal outcomes (although, our study does not find a statistically significant effect of a two-voter system on elementary literacy rates).
Keywords: 330